Psychosocial Attributes and Financial Self-Efficacy Among Older Adults - Sarah D Asebedo (Journal of Financial Therapy, 2019)
This study investigates the relationship between psychosocial characteristics and financial self-efficacy (FSE) within a sample of 9,187 U.S. individuals over age 50 from the Health and Retirement Study. Psychosocial factors were operationalized through the PERMA well-being construct from positive psychology: positive emotions, engagement, relationships, meaning, and accomplishment. Results of a second-order confirmatory factory analysis (CFA) within a structural equation modeling framework revealed that the PERMA construct was positively associated with FSE for the full sample, the spouse/partner sample, and the sample with children. Results also indicated that all individual PERMA elements were directly and positively associated with FSE except for engagement, which revealed a direct negative relationship. Researchers have found older adults’ FSE to be vulnerable to a sustained decline; this study builds upon the literature by providing insight into how the psychosocial environment might contribute to or mitigate this decline.
Keywords: Financial Self-Efficacy; Older Adults; PERMA Well Being; Positive Psychology; Psychosocial